Comparison among anorexia nervosa adolescents with or without previous overweight, obese, and healthy adolescents - Amianto, Federico; Sertori, Francesca; Davico, Chiara; Marcotulli, Daniele; Vitiello, Benedetto (Frontiers in Psychiatry, 2024)
Background: Anorexia nervosa (AN) and obesity (OB) are relevant concerns in adolescence. Despite their contrasting phenotypes, they share common pathogenic origins and may be present in the same individual at different times. We explored the psychopathology and attachment features of adolescents with AN who did (AN-ow) or did not (AN-nw) have previous overweight, compared with OB adolescents and healthy control (HC) adolescents.In total, 148 female adolescents referred to an outpatient clinic for an eating disorder (66 for AN and 42 for OB) and 40 HCs were assessed using self-administered instruments that measured parenting, attachment, eating, and general psychopathology.Group differences were tested by analysis of covariance, and correlations between variables were examined.